Formulating productive marketing communications strategy: a major health system's experience - James K. Elrod; John L. Fortenberry (BMC, 2018)
Abstract Background Healthcare establishments serve as key community resources, bringing into locales a wealth of resources aimed at enhancing and improving health and wellness. Without effective communications, current and prospective patients will remain unaware of available offerings, foiling opportunities for mutually beneficial exchange. Today, healthcare organizations engage audiences by selecting from among the components of the marketing communications mix, but this wasn't always the case. There was a time not long ago when communications options were limited due to industry traditions, creating associated challenges. Discussion Willis-Knighton Health System faced a communications dilemma in the 1970s when, as a small healthcare provider desirous of growth, it could not achieve a satisfactory media presence via the usual and customary route of the day: submitting press releases to news media organizations, requesting conveyance of associated stories to their audiences. This forced the institution to explore other possibilities, ultimately leading it to experiment with and embrace advertising at a time period when its use was generally shunned in the industry. Willis-Knighton Health System's pioneering deployment of advertising helped the institution achieve its intended promotions goals, supplying mutual benefits and affording insights which influence its communications approach to this day. Conclusions Deploying advertising years in advance of its widespread acceptance and use in the healthcare industry, Willis-Knighton Health System forged new pathways and acquired experience which fostered provider-patient engagement initiatives, affording an enduring marketing communications approach. Challenging situations are quite common in the healthcare industry and the one faced by Willis-Knighton Health System was no exception, but it supplied an immense opportunity to innovate, leading to communications prowess, resulting growth, informed audiences, and lasting mutual benefits.